Dude, Where’s My Data? The Effectiveness of Laws Governing Data Breaches in Australia - Hile, Jack (Journal of Telecommunications and the Digital Economy, 2021)
The increasing prevalence of large-scale data breaches prompted Australia to strengthen the Privacy Act by enacting the Privacy Amendment (Notifiable Data Breaches) Act to regulate the behaviour of entities entrusted with personal data. However, this paper argues that these legislative instruments are ineffective when dealing with data breaches and their associated problems. In supporting this conclusion, this paper first develops a criterion for effective data breach law, and then evaluates the Australian framework against this criterion to determine its operational effectiveness. In addition, this paper analyses practical developments in the area of data-breach law to garner insights as to how the Australian framework can be made more effective. Ultimately, this paper concludes that the Australian framework is ineffective when dealing with large-scale data breaches, and recommends future legislative amendment as a means of bolstering its effectiveness.